The Effect Of Added Market Value On Stock Pricing Efficiency According To The Sharpe Model - Jassim AL-Maliky, Ghadeer; Mustafa Hassan, Anwar (Journal of Economics and Administrative Sciences, 2024)
The main objective of the research is to study the effect of added market value on the efficiency of stock prices according to the Sharpe model for pricing corporate stocks, according to what emerged from the literature review at the theoretical level, including previous studies, and to deduce its trends associated with the power of interpretation predicted by the research hypotheses in their content related to the impact of value. Added market value to the efficiency of stock prices of the companies studied at the level of the industrial sector in the Iraqi Stock Exchange. A sample was tested using a purposive sampling method that included (13) thirteen industrial companies contributing to the Iraqi Stock Exchange out of (21) twenty-one industrial companies. Over the time horizon of the research, which is (13) thirteen years (2010-2022), then the variables were measured and analyzed at the financial and statistical levels, described and interpreted using the double data method (panel data) to show the impact of the time series, as well as using description and inference tools. Statisticians, including measures of central tendency and dispersion in relation to the results of statistical description, correlation and regression as far as interpretation and inference are concerned, and after conducting mathematical analyzes of the studied company data and testing the research hypothesis in the selected sample, a number of results were reached, including the effect of the added market value owned by the companies Directly with the company’s stock prices according to the use of the Sharpe model for stock pricing, and companies that have an added market value have high stock prices as a result of their possession of a high market value and thus a distinctive position among other competitors. Also, companies that have an added market value achieve large profits, and it is Then the research came out with a number of recommendations, paying attention to the availability and measurement of the added market value of Iraqi industrial companies contributing to the Iraqi stock market, which contributes to maximizing the companies’ stock prices. The research also came up with a number of future studies that require other designs in the way of scientific investigation and an attempt to improve the theory. . Paper type: Research paper